Acreditation of Research Ethics Committees, as part of a process - Fuentes, Duilio (2007)
The research ethics committee plays an important role in the protection, wellbeing and security of research participants. This role is more important in countries where the population has the potential of being vulnerable to exploitation. In presence of this fact and considering the existence of serious problems with the necessity of subjects protection system reform, the need of shared quality standards and appropriate criteria is posed, creating the term ‘accreditation’. Knowing local reality and trying to understand the meaning of accreditation of research ethics committee as a process, its execution is justified and a strength/ weakness analyses is done in the event it is performed by a government entity.